(untitled) (Research, Society and Development, 2025)
This study aims to report the experience of healthcare professionals regarding the management and deployment of electronic dispensaries in the care sectors of a public hospital in the state of São Paulo, Brazil. This is a qualitative, descriptive, experience-report study conducted in October 2025 as part of hospital management activities. The implementation of electronic dispensaries in these sectors has yielded significant advances. Therefore, the implementation has proven to be an effective strategy for modernizing care practices, strengthening resource management and patient safety.